Sustainable postharvest solutions: Enhancing potato quality with whey protein-based edible coatings - Obeidat, Hadeel; Tarawneh, Haneen; Alrabadi, Nizar I; Alu’datt, Muhammad H; Hawamdeh, Sameerah; Alrosan, Mohammad (Edelweiss Applied Science and Technology, 2026)
Postharvest food loss and sustainability are important issues in the storage of potatoes. Edible coatings, specifically whey protein concentrate (WPC), are environmentally friendly options that can be used to maintain quality. This study examined the effectiveness of the WPC coating in ensuring quality in potato tubers when in storage. Potatoes that were fresh, even-sized, and free of defects were divided into three groups: the control (T1), which had no coating; WPC-coated (T2); and composite WPC-coated (T3). The potatoes were stored for 60 days under ambient conditions (25 °C, 55% relative humidity), refrigeration (4 °C), and controlled conditions (20 °C, 74% relative humidity). Sensory assessment was carried out at regular intervals by use of the 5-point hedonic scale. Uncoated tubers (T1) started showing wrinkling and decay on Day 28, and the condition worsened with time under all conditions. On the other hand, the coated potatoes (T2 and T3) stayed smooth and acceptable in appearance until the end of storage. Statistical Analysis showed a significant difference between coated and non-coated potatoes, but not between T2 and T3. It can be concluded from this experiment that coating of potatoes using whey protein concentrate (WPC) is an environmentally friendly way to prolong shelf life.